Factors Influencing the Utilization of the Free Health Check-Up Service Program Among Adults in Medan City in 2026 - Humaira Nasution; Juanita Juanita; Destanul Aulia (International Journal of Health and Medicine, 2026)
The Free Health Check-Up Program (CKG) is a promotive and preventive government policy aimed at improving early detection of non-communicable diseases among adults. However, the utilization of the CKG program in Medan City remains suboptimal despite the community’s positive perception regarding the importance of health screening. This study aimed to analyze the factors influencing the utilization of the CKG program among adults in Medan City, including knowledge, attitude, family support, access to health services, the role of health workers, perceived need, and evaluated need. This research employed a quantitative approach with a cross-sectional design. The study population consisted of 17,724 participants of the CKG program from five community health centers in Medan City, with a sample of 392 respondents selected using accidental sampling techniques. Data were collected using structured questionnaires that had been tested for validity and reliability. Data analysis was conducted through univariate, bivariate, and multivariate analyses using multiple logistic regression. The simultaneous analysis showed that all variables in the model had a significant effect on the utilization of the CKG program, with a model contribution of 65.8% (Nagelkerke R Square = 0.658). Knowledge was identified as the most dominant factor influencing the utilization of the CKG program, with a regression coefficient of 1.579. The findings indicated that better respondent knowledge regarding the benefits and procedures of the CKG program increased the likelihood of utilizing the health service. In addition, attitude, family support, access to health services, the role of health workers, perceived need, and evaluated need also contributed significantly to the individual's decision to utilize preventive health services. This study concludes that improving inclusive health education, optimizing primary health care services, and integrating health data such as Electronic Medical Records (EMR) are essential to increase the utilization of the CKG program among adults in Medan City.